Expansão da cidade, legislação urbanística e propriedade imobiliária: uma análise de São José do Pinhais - Junqueira, Camila Simoni (2018)
The present research aims to analyze the legal aspects by which the production of condominiums, in São José dos Pinhais, has been shown as the preferred modality of urbanization by real estate owners, in the detriment of allotments. For this, the dissertation presents a theoretical framework of the real estate property, the social function of property and the legal forms of appropriation of urban properties, namely, allotment and condominium. It was briefly explained about the social and urban impacts of the implementation of condominiums. From the data provided by the Municipality of São José dos Pinhais, all condominiums existing in the Municipality were analyzed and spatialized. It was observed that allotments were the preferred modality of urbanization in São José dos Pinhais until 1980. Between 1980 and the mid-1990s real estate production was stagnant in the Municipality. From the mid- 1996s onwards, the production of condominial units gradually increased until, in the years 2000, it exceeded the production of lots. Instead of promoting a better use of a lot, currently in São José dos Pinhais, large condominiums are being built on large non-lot lands. It is concluded that the condominiums are a modality of urbanization much less burdensome for real estate developers because they do not require the donation of areas to the municipality, allow a subdivision of land smaller than the minimum required by zoning and for having a procedure of more simplified approval. There is a necessity to better regulate the use of the property through the obligation to implement the allotment before allowing the construction of buildings.